The Tradition of Rokat Pandhabâ Pangantanan: A Historical Development of Islam in The Cross Culture of Hindu in Bringin Dasuk Village, Sumenep, Madura in 17th Century - Riadi, Ach. (Journal of Islamic History, 2021)
Islam is a blessing for the universe. Islam is a present and accepted in a long process. Assimilation, acculturation, and conferences with similar social dimensions occur in the archipelago. Like Islam, it entered Madura through the sea around Parindu Beach, south coast of Sumenep Madura. Penetration Pasifique, the Islamic way of engaging in cultural battles with residents in Sumenep, Madura. Therefore, in its development, Islam has succeeded in basing the teachings of the Qur’an and Hadith through cross-cultural found in local traditions in Bringin village, Sumenep District, Madura Regency. This research is a historical study of the development of Islam in Sumenep, Madura through the local tradition of Rokat Panḍhâbâ Pangantanan in Bringin Village, Dasuk District, Sumenep, Madura. The theory of Milanowski’s functionalism is used to find meanings and uses in two cross-cultural relationships of Islam and Hinduism that are believed by the practitioners of the local tradition of Rokat Panḍhâbâ Pangantanan. Qualitative research methods and historical approaches are applied using comparative study techniques including sociology, anthropology-culture, philology, and multidimensionality.